Development and validation of scenarios for the assessment of project management people competences - Souza, Mariane C. (2022)
The development of project management competences, particularly people competences, is a challenging and complex process. Scenario-based learning is an interesting approach to developing these competences, involving real problems that allow you to face challenges based on your own experience. In this sense, scenarios act as the starting point for diving into a real-world problem and fostering the whole process of decision making and searching for solutions. The International Project Management Association (IPMA) has defined an Individual Competence Baseline (ICB 4.0) standard for the development of the project management area of knowledge. The standard shows, besides other competences, the following 10 people competences: personal communication; leadership; teamwork; self-reflection and self-management; personal integrity and reliability; relationships and engagement; resourcefulness; conflict and crisis; negotiation; and result orientation. Development and assessment of these competences are increasingly important for the people working on projects. In addition, there is an accreditation process for these professionals that is increasingly required by organizations. The process involves an assessment of technical qualifications to improve task performance. In this sense, this paper aims to describe the development and validation of ten project management scenarios that allow the assessment of people competences. The methodology of the study comprised six phases. In addition, two pilot applications were conducted with the proposal to assess competence of the scenarios developed. The findings reveal that the scenarios can be used as an alternative approach to the accreditation process of professionals who work in project management.